Accessibility Of People With Disabilities To Public Facilities In Yogyakarta City - Aan Qur'ana; Eko Purnomo (Journal of Politics and Policy, 2020)
Persons with disabilities, those who have physical limitations so that they have difficulty doing daily activities. Accessibility is very important for people with disabilities because it is to get the same with non-disabled people. The available facilities must also look at the surrounding community, so that all communities can experience the facilities. That way the existing facilities must be able to meet the needs of persons with disabilities in order to facilitate their access. That way this research aims to analyze the existing facilities in the city of Yogyakarta is adequate or not. The facilities examined here are such as sidewalks, public transportation in the form of Trans Jogja buses and also education in the city of Yogyakarta. In addition, several concepts related to accessibility and public facilities for people with disabilities also use the right approach. Through a qualitative descriptive analysis of accessibility and public facilities for persons with disabilities that are already expected to be able to facilitate and is expected to be designed according to needs. Starting from the design of transportation, education as well as the place of recreation. Therefore, these interests must pay attention to and consider designs that can be accessed by persons with disabilities.Keywords: Accessibility, Public Facilities, People with Disabilities.